Purification and characterization of the RfpA phytochrome of a thermophilic cyanobacterium - Ahmed, Syeda Josna (2024)
Perceiving light is a crucial step for all photosynthetic organisms. This perception of light is mediated by a group of photoreceptor proteins called phytochrome that exhibit high responsiveness to light and govern other biological processes like growth and development in plants, bacteria, fungi, algae, and cyanobacteria. They utilize red light and far-red light to regulate different light-dependent cellular processes. Certain cyanobacteria contain a distinct phytochrome called RfpA, which enables them to carry out photosynthesis by harnessing far-red light. So far there is no structural-functional relationship is known about this protein. The aim of this study was to purify RfpA to explore its signaling mechanism and spectral characterization to observe the photocycle of the phytochrome. Due to the difficulties in the purification of full-length protein, we constructed three different versions of the protein varying in length and containing different domains (GAF-PHY-PAS, GAF-PHY, and GAF only) using site-directed mutagenesis. Although our primary goal was the purification of the full-length protein, we attempted to obtain the longest possible fragment of the protein. We successfully managed to purify GAF-PHY and GAF mutants by affinity and size exclusion chromatography. Furthermore, UV-Vis spectroscopy was performed to study the photocycle of the protein. Spectroscopy study highlights that RfpA protein exists predominantly in Pfr (Far-red light absorbing form) as its resting state, denoting the characteristics of a bathy phytochrome. These findings provide remarkable insight into the unique spectral properties of RfpA, which can be beneficial in developing optogenetic tools and biotechnological applications.